On the taxonomy of the genus Agrisius Walker, 1855, with descriptions of two new species from Vietnam and Laos (Lepidoptera, Erebidae, Arctiinae) - Volynkin, Anton V.; Dubatolov, Vladimir V.; Kishida, Yasunori (Zootaxa, 2018)
Two new species of the genus Agrisius Walker, 1855, A. orhanti Volynkin, Dubatolov & Kishida, sp. n. and A. leloii Volynkin, Dubatolov & Kishida, sp. n. are described from South Laos and Vietnam respectively. A. orhanti sp. n. belongs to the A. japonicus Leech, 1889 species-group. Whereas, the male genitalia structure of A. leloii sp. n. is intermediate between those of the A. japonicus and the A. guttivitta Walker, 1855 species-groups, therefore, it is assigned to a separated species-group (the A. leloii species-group). Agrisius dubatolovi Orhant, 2012 is downgraded as a subspecies of A. japonicus: Agrisius japonicus dubatolovi Orhant, 2012, stat. nov. Female genitalia of species of the A. japonicus and most of the A. guttivitta species-groups are illustrated for the first time.